A THEORETICAL APPROACH TO MEASURING ENVIRONMENTALLY SUSTAINABLE GROWTH OF AGRICULTURE - Lina LAURAITIENĖ; Vlada VITUNSKIENĖ (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
In recent years, the economic growth has resulted in the depletion of natural resources and degradation of ecosystems. Therefore, the environmentally sustainable growth was accepted, as a new mode for economics, that prevents environmental deterioration and loss of biodiversity. The idea of environmentally sustainable growth has been widely discussed not only by experts in environmental economics, but also in the international and national policy scene. However, the measurement of environmentally sustainable growth still remains a challenge, especially in agriculture. In this paper, available academic literature is reviewed and summarized to provide a theoretical baseline for creating a measure of environmentally sustainable growth of agriculture.